Associations between humility, spiritual transcendence, and forgiveness - Powers, Christie (Research in the social scientific study of religion, 2007)
Humility may play an important role in the forgiveness process. For example, awareness that one is not superior to others or the propensity to acknowledge mistakes could facilitate forgiveness. However, virtually no empirical research has examined possible connections between dispositional humility and different attitudes toward forgiveness or tendencies to forgive. Toward this end, undergraduates completed self-report measures of humility and forgiveness, and some dimensions known to correlate with self-reported forgiveness [e.g., spiritual transcendence (ST) and socially desirable responding]. Participants also completed Humility and Self-Esteem Implicit Association Tests. As predicted, moderate positive correlations were found between humility, ST, and forgiveness (when controlling for desirable responding). In particular, self-report measures of humility correlated highly with the self-reported tendency to forgive, whereas implicit humility correlated more strongly with attitudes towards forgiveness. No evidence of statistical mediation was found. That is, the positive humility-forgiveness associations remained when ST was controlled, and positive spiritual transcendence-forgiveness associations remained when humility was controlled. Finally, a statistical interaction between humility and ST was detected on self-reported likelihood of forgiving. When controlling for socially desirable responding, people with a combination of high humility and high spiritual transcendence self-reported being more likely to forgive than persons with any other combination of humility and ST. Taken together, these patterns offer some clues about the positive nature of humility and have implications for interventions aimed at increasing forgiving behaviors.